Perception of social media use for information service delivery in University Libraries: a case study of Kenneth Dike Library, University of Ibadan (2022)
Purpose: As one of the first university libraries to embrace ICT adoption in the country, it was necessary to ascertain how the library is faring in terms of digital services provision using social media tools. Methodology: The survey design was applied alongside the accidental/convenient sampling technique. The population comprised 300 library patrons and library personnel in KDL. The method of data gathering was the questionnaire. Two hundred and thirty-three (233:77.7%) response rate was observed. The descriptive and inferential statistical tools were applied. Findings: patrons were positive about the provision of certain services using SMTs, but in terms of actual use, there was a lack of interest. Similarly, there was a low frequency of the use of available SMTs in the library; however, Facebook was the most utilized SMT by patrons, followed by Blog. The paper concludes that it is not enough to deploy relevant SMTs but to develop patron-focused services that will endear patrons to use them. Originality/value: It is an in-depth case study that explored patrons’ disposition towards information service delivery using available social media tools in KDL.